Per Capita Consumption and Growth - Fei, John C. H. (Quarterly Journal of Economics, 1965)
Introduction, 52. — I. The CPCS model of growth, 54. — II. Growth in the labor-surplus type of underdeveloped economy, 60. — III. Revision of the consumption standard, 62. — IV. The long-run growth target, 65. — V. The average propensity to save and the dynamic production efficiency, 68. — VI. Growth under imperfect knowledge, 70.